Penyelesaian Hukum Terhadap Pengalihan Tanah Adat dalam Proyek Strategis Nasional Food Estate Perspektif Mashlahah Mursalah - Mahmud Almizan Daulay; Tetty Marlina Tarigan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The development of food estates has significant impacts on customary forests and the rights of indigenous peoples. The main objective of this study is to ensure that there is a legal settlement of the transfer of customary land in the context of national strategic projects, with a mashlahah mursalah perspective. In this case, mashlahah mursalah means prioritizing public interest and avoiding harm that may be caused by food estate policies or projects. This research is a normative research (legal research) that uses a conceptual approach and a statute approach. Primary data is obtained from laws while secondary data is used to assist the analysis obtained through books, legal journals, or expert opinions. The results of the study indicate that the transfer of customary land forests in the food estate project can cause harm to indigenous communities, including indigenous communities losing their customary land rights. The research results show the need for better enforcement of legal protection for customary land in national strategic projects. By ensuring that the decision-making process involves indigenous peoples and takes into account their interests and rights.